The twelve jays of Christmas [compact disc, unabridged] : a Meg Langslow mystery - Andrews, Donna (Andrews, Donna. Meg Langslow mysteries., 2021)
When a blizzard traps her brother Rob and his fiancée Delaney's guests inside during their Christmas party, Meg must help the snowbound would-be eloping couple thwart their mothers' grandiose wedding plans and solve a murder among the assembled friends and relatives.